Anti-Hadith: Rujukan Kepada Kitab Jima’ Al-’Ilm - Ali, Abdul Karim (Jurnal Usuluddin, 1999)
The article attempts to introduce the paramount importance of kitab Jima’ al-’Ilm written by al-Shafi’i in relation with the emergence of anti-hadith. This book contains dialogue and debates that have taken place between al-Shafi’i and his opponents and considered as the earliest document indicates the existing certain groups or individuals that questioned or repudiated the authority of hadith. It also tries to identify the unnamed opponents that have disputation with al-Shafi’i.